Morfometrik Sistem Pencernaan Ikan Nila (Oreochromis niloticus) yang Dipapar Limbah Cair Kelapa Sawit - Yusrizal Akmal; Cut Mutia Sena Devi; M Muliari; Rindhira Humairani; Ilham Zulfahmi (Fapetrik-UMPAR, 2021)
Liquid waste is one of the negative impacts of the oil palm processing industry, which can disrupt aquatic ecosystems. This study aims to describe the morphometric conditions of the digestion system of tilapia (Oreochromis niloticus) exposed to palm oil wastewater. The study was conducted from April to July 2020. Tilapia measuring 4-7 cm in length with an average weight of 3-8 grams with 160 fish per treatment. The stages of the research included raising fish, giving oil palm liquid waste, and observing the morphometric digestion system. Fish were exposed to oil palm wastewater with concentrations of 0 mL.L-1, 47 mL.L-1, 70.4 mL.L-1, and 94 mL.L-1 for 64 days. The analysis was carried out on the Gastro Somatic Index (GaSI), Intestine Somatic Index (ISI), Relative Gut Lengths (RGL), Relative Intestine Lengths (RIL), and Hepato Somatic Index (HSI). The results showed that palm oil wastewater could affect the morphometric digestion of tilapia (Oreochromis niloticus). Palm oil wastewater with a concentration of 94 mL.L-1 also affected the GAS of 2.40%, the ISI of 5.49%, and RIL of 549.11%. In the treatment, the concentration of oil palm liquid waste was 70.4 mL. L-1 affected the HSI by 1.70%. However, exposure to palm oil wastewater does not affect RGL. The content of palm oil liquid waste can disrupt the metabolism of the stomach, intestinal, and liver cells. The high concentration of waste can damage the lining of the stomach and intestines, resulting in decreased appetite.